Kajian Socio Legal Pengaturan Partisipasi Publik dalam Penyusunan Rancangan Peraturan Daerah - Saru Arifin (Perspektif Hukum, 2018)
Community participation is one of the important pillars in good governance. In the context of the formation of participatory local regulations. This study aims to analyze how the pattern of community participation, what forms of community participation and who are the actors of community participation in the process of forming local regulations. This type of research is socio-legal using primary and secondary data. The results of this study indicate that the pattern of community participation in the formation of regional regulations is carried out through interactive participation methods both through mass media, seminars and work visits to constituents during recess. The forms of community participation carried out in the formation of local regulations are public hearings, musrenbang and consultations. While the participation actors involved in the formation of regional regulations are constituents, SKPD, academics and the general public. The obstacles found in the process of community participation are the lack of understanding of the actors of participation in the substance of the draft regional regulations discussed so that they are less effective, and the limited actors of participation in the constituents.